Penguatkuasa VHF Menggunakan Mosfet Kuasa - Abu Hasan, Juniah (Universiti Sains Malaysia, 2006)
These research involved the design of the VHF power amplifier by simulation using the RF Power MOSFET. Those design used two types of software such as Advanced Design System and Z-Match. RF Power MOSFET are used in communications equipment from 2 to 400 MHZ with power level from 1 watt to over 100 watt. The frequency of 300 MHz had been choosen for the purpose of the power amplifier design. The transistor’s model that had been used is MRF136 from Motorola. These transistor had been choosed to ensure the stability so that the oscillation will not occured that can cause malfunction to the power amplifier. Through the stability test that had been carried out, it showed that the transistor MRF136 from Motorola is stable and suitable for the power amplifier design at frequency of 300 MHz. The technique that had been used to design power amplifier was by using the Conjugate Matching. The purpose of conjugate matching is to get the maximum gain at the output. There are also another techniques to design power amplifier such as Load Line Matching and Load Line Analysis. However, only the conjugate matching technique had been carried out.